MANAJEMEN MUTU PENDIDIKAN DALAM MENGHADAPI KREATIVITAS ANAK - Syahril Chaniago (Fakultas Ekonomi Universitas Negeri Jakarta, 2012)
ABSTRACTMany people in society are not satisfied with the quality of education in our country. Obviously we often hear phrases like,